2012
DOI: 10.17221/192/2011-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different light intensities on anti-oxidative enzyme activity, quality and biomass in lettuce

Abstract: Weiguo Fu, Pingping Li, Yanyou Wu, Jianjian Tang, 2012. Effects of different light intensities on anti-oxidative enzyme activity, quality and biomass in lettuce. Hort. Sci. (Prague), 39: 129-134.Recently, the worldwide demand for romaine lettuce (Lactuca sativa L.) has been increasing. Thus, regulation measures of supplementary or shading light are often used in the production of lettuce in some regions. However, inconsistent results on the light saturation point of lettuce from previous studies do not facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 18 publications
3
18
0
4
Order By: Relevance
“…Nitrogen use efficiency (NUE) and growth, if not by nitrate/nitrogen itself, can be influenced by light [36]. When light, and in particular DLI, exceeds the light saturation point of lettuce, it can cause photoinhibition and decrease NUE, compromising lettuce growth and development, and significantly affecting fresh yield [37,38]. The optimal DLI for lettuce plants ranges between 10 and 17 mol m 2 d −1 and we used 18.1 DLI to boost lettuce growth.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen use efficiency (NUE) and growth, if not by nitrate/nitrogen itself, can be influenced by light [36]. When light, and in particular DLI, exceeds the light saturation point of lettuce, it can cause photoinhibition and decrease NUE, compromising lettuce growth and development, and significantly affecting fresh yield [37,38]. The optimal DLI for lettuce plants ranges between 10 and 17 mol m 2 d −1 and we used 18.1 DLI to boost lettuce growth.…”
Section: Discussionmentioning
confidence: 99%
“…Light fosters lettuce growth only in a specific range of light intensities [19]. Several studies have shown that lettuce grown in summer with light intensity over 600 µmol m −2 s −1 had reduced biomass, leaf area and chlorophyll content [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, light caused an increase of carotenoid content in chia seedlings and therefore increased their antioxidative properties. Lower light intensity in a range from 100 to 300 µmol m −2 s −1 had a positive effect on photosynthetic processes [35], increased chlorophyll content [36], and more effective light use [37] in plants. In this study, we used the light intensity of 100 µmol photons m −2 s −1 , which generally has a beneficiary effect on the synthesis of different investigated bioactive compounds and enhances antioxidative properties in chia microgreens.…”
Section: Effect Of Illumination On Carotenoid and Chlorophyll Contentmentioning
confidence: 94%